A landscape triage approach: combining spatial and temporal dynamics to prioritize restoration and conservation. Issue 3 (15th March 2015) - Rappaport, Danielle I.; Tambosi, Leandro R.; Metzger, Jean P.; Cadotte, Marc
Summary The spatial and temporal dynamics of landscape structure yield ecological constraints that may limit or promote the recovery of functioning habitat within human‐modified ecosystems. In planning restoration and conservation measures to optimize outcomes for biodiversity, such constraints should be evaluated at multiple scales. This study presents a multi‐scale methodology based on the concept of triage that incorporates landscape and regional spatial context and temporal dynamics to prioritize restoration and conservation. In applying the framework to a large Brazilian Atlantic forest study site that underwent substantial forest cover changes between 1990 and 2002, our results demonstrate the utility of this framework for navigating between different trade‐offs inherent to biodiversity conservation. Landscapes are ranked in accordance with indicators that evaluate the relative urgency of intervention, feasibility of recovery and importance for broader‐scale biotic flows. Synthesis and applications. Efforts to enhance biodiversity through restoration and/or conservation may be hampered when decisions are based exclusively on contemporary landscape structure, and not made through a historical perspective. In making such trade‐offs explicit, this framework can aid practitioners in defining the most appropriate set of restoration or conservation strategies given the ecological constraints, biodiversity goals and available budget.